Remembering Professor Marc Krasner - Vuković, Mirjana (Sarajevo Journal of Mathematics, 2024)
It is thirty years since Marc Krasner, Professor and Professor emeritus of the University “Pierre et Marie Curie” from Paris passed away. Marc Krasner, a Russian–born, eminent French mathematician of Jewish origin began the life in Odessa on April 9, 1912, and died on May 13, 1985, in Paris. Marc Krasner received in 1938 his PhD, from University of Paris – Sorbonne under Jacques Hadamard, with thesis “Sur la th´eorie de la ramification des id´eaux de corps non–galoisiens des nombres alg´ebriques.” From 1937 to 1960 he was a scientist at CNRS (French National Center for Scientific Research) and from 1960 professor at the University of Clermont–Ferrand. In 1965 Krasner was appointed a full professor at the University “Pierre et Marie Curie” – Paris VI, from which he retired as professor emeritus, in 1980.